Overview and Tools of Asset Management in Renewable Energy Based Smart Grid - Salkuti, Surender Reddy (International Journal of Engineering and Technology, 2018)
This paper presents the importance, issues and challenges related to Smart Grid. It also evaluates various approaches for Smart Grid planning and operation. It discusses tools for asset management and their applicability to the next generation grid. The proper asset management reduces the risk of equipment failure, extends the equipment life and minimizes the occurrence of unplanned outages. Aging assets, uncertainty in load demand profile and renewable energy resources, and demand management create a challenge for the optimal operation and maintenance of electrical grid. Frequent condition assessment with asset audit enables a comprehensive assessment of the asset in question and includes objective and transparent asset condition information recommendations for the improved environmental sustainability. This paper addresses the challenges and opportunities to improve transmission and distribution systems asset maintenance. This paper also presents the asset replacement alternatives. It presents the cost-benefit analysis of asset management using the information/real time data from the utility company. This paper will serve a guide for doing the asset management to the electrification  process, investment and  recovery to sustain reliable and efficient power delivery.